Plasma-derived C1 esterase inhibitor for acute antibody-mediated rejection following kidney transplantation: Results of a randomized double-blind placebo-controlled pilot study - Montgomery, Robert; Sommerer, Claudia (American journal of transplantation, 2016)
Antibody-mediated rejection (AMR) is typically treated with plasmapheresis (PP) and intravenous immunoglobulin (standard of care; SOC); however, there is an unmet need for more effective therapy. We report a phase 2b, multicenter double-blind randomized placebo-controlled pilot study to evaluate the use of human plasma-derived C1 esterase inhibitor (C1 INH) as add-on therapy to SOC for AMR. Eighteen patients received 20 000 units of C1 INH or placebo (C1 INH n = 9, placebo n = 9) in divided doses every other day for 2 weeks. No discontinuations, graft losses, deaths, or study drug-related serious adverse events occurred. While the study's primary end point, a difference between groups in day 20 pathology or graft survival, was not achieved, the C1 INH group demonstrated a trend toward sustained improvement in renal function. Six-month biopsies performed in 14 subjects (C1 INH = 7, placebo = 7) showed no transplant glomerulopathy (TG) (PTC+cg≥1b) in the C1 INH group, whereas 3 of 7 placebo subjects had TG. Endogenous C1 INH measured before and after PP demonstrated decreased functional C1 INH serum concentration by 43.3% (p < 0.05) for both cohorts (C1 INH and placebo) associated with PP, although exogenous C1 INH-treated patients achieved supraphysiological levels throughout. This new finding suggests that C1 INH replacement may be useful in the treatment of AMR.